Studies on the Prodigiosin Production from Streptomyces coelicolor in Liquid Media by Using Heated Lactobacillus rhamnosus - Huy NA Do and Tu H K Nguyen (Journal of Applied Pharmaceutical Science, 2014)
Prodigiosin (PG) is not only an antibiotic but it has also been characterized immunosuppressive and anticancer activities. Prodigiosin is produced by Streptomyces coelicolor and Seratia marcescens. In this study, prodigiosin (PG) production of S. coelicolor was optimized using 50µL, 100µL of heated cells at 70oC and 100oC of Lactobacillus rhamnosus. With 50µL heat-killed cells at 70oC L. rhamnosus, prodigiosin (PG) production of S. coelicolor enhanced the maximum prodigiosin concentration (9.79 ± 1.68 mg/L) by six-fold at the early stage in the second day incubation in the comparison with prodigiosin (PG) production of S. coelicolor without heated L. rhamnosus (1.43 ± 0.22 mg/L). There were the affects of the components of L. rhamnosus on PG production. This is the first report that L. rhamnosus affecting on PG production in S. coelicolor.
Keywords: Lactobacillus rhamnosus, prodigiosin, Streptomyces coelicolor.